Designing Contextual, Localised Learning School Model to Improve the Quality of Pupils' English Learning in Rural Schools in Sambas Regency - Marwinda Siska; Dedi Irwan; M.Iqbal Ripo Putra (IKIP PGRI Pontianak, 2023)
This study aims to develop a model to improve the quality of StL schools this is to ensure that it can be applied at schools in Sambas Regency under the challenging needs and potentials they have, based on the school perspective. The result of this study is expected to provide description of the How far has the activities included in StL model been applied by school, what challenges did rural schools face in implementing the activities of StL model, how is StL model which could be apply in rural schools locally and contextually. This research was multiple case study conducted using a descriptive qualitative approach involving 4 schools spread across Sambas Regency, namely in rural areas. In this case, the 4 schools are middle schools which include 2 different districts, namely Sebawi District and Tebas District. Tool of data collection was interview guidance, and the data analysis using thematic analysis and cross case analysis techniques. The result of this study is recommendation for improving the application of StL model been applied by considering which StL model that could be apply locally, contextually and the challenges found by schools in implementing StL model.